Design and Development of High-Speed and High-Power Drive Motor for Heavy Commercial Vehicle - Kong, Weifeng; Huang, Shengtao; Wu, Wenchao (2022 IEEE 5th International Electrical and Energy Conference (CIEEC), 2022)
In order to meet the performance requirements of the power system of heavy-duty commercial vehicles, a special drive motor is designed in this paper, which has the characteristics of high speed, heavy load, and continuous high power. The permanent magnet synchronous motor is selected, and an optimized design is made for the motor components including stator and rotor punching, winding, rotating shaft, cooling system, sealing structure, etc. The accurate simulation and analysis methods are used to calculate and check. Finally, after the prototype test, all the indexes meet the design requirements. Compared with a low-speed and high-power motor, the design results have obvious performance advantages.